IoT TROHEMS ( Transformator Online Health Monitoring System) - Tianur; Borahima, Mahdi Lestari; Endri Widodo (Politeknik Caltex Riau, 2023)
The transformator is a very important component in the distribution of electricity from distribution substations to consumers. Damage to the transformator causes the continuity of service to consumers to be disrupted, electricity energy is not sold to consumers and the high price of transformators makes this component really need special attention. In the world of industry, transformators are a vital part of the equipment because they are the main source of electrical energy. Even though they have other energy sources from generators as a backup, generators that use diesel engines have a certain time limit for their use depending on the capacity of each fuel tank they have. If there is a failure in the two systems, industrial operations will stop and this can cause the company's image to become unfavorable.To overcome the potential losses that occur due to transformator failure and to increase the reliability of transformators, a real-time monitoring system based on IoT (Internet of Things) is needed.To conduct this research, the authors used the fishbone issue method to determine the factors causing the dominant occurrence of burnt transformers and used the Arduino Uno Wifi Rev2 for monitoring on the transformer side and used the Raspberry PI CM4 to monitor power measurements on the MCC. System Monitoring is designed using Node-RED IoT as a data processor, using Influxdb as a database, using MQTT as a hosting server, and Grafana as a Dashboard platform. With the creation of a realtime monitoring system for transformators, it is hoped that the maintenance system for transformators will be better so that they can anticipate transformators without starting a burn out first. The results of the monitoring system development resulted in a decrease in the risk map from a score of 16 (high) to 4 (low to moderate). In references to similar studies, it was found that no one monitors the critical parameters of the transformer more fully, as in this study monitoring from the transformer side: temperature, oil sudden pressure, oil level and on the mcc panel: voltage, current, power, frequency, and cosphi , equipped with a trip system. Keywords: internet of things, nodered, influxdb, MQTT, grafana, transformator health monitoring